A comparative study on the impact of different fluxes in a discontinuous Galerkin scheme for the 2D shallow water equations - Rasolofoson, Faraniaina (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.